Spațiul public și organizațiile. O abordare din perspectiva comunicării - Rosemarie HAINEŞ (Revista Transilvană de Ştiinţe Administrative, 2008)
The current study captures several important stages in the evolution of organisation research, as it takes into consideration the phenomenon of communication to be in a relationship of complementary and inter-relation in the phenomenon of organisation. In order to be performed, the act of communication requires a situation, a context; likewise, organisations cannot exist outside communication, which leads to transformation and change. During the XIX-th centurzm the enterprise was seen as a space for production; at the beginning of the XX-th century the enterpriseemerges as an organisation and as a model of organisation. In the 1990’s; the frameworks for organization analyses have known new developments. The concept of „system” was replaced by that of composite assembly. The notion of „social field” (cf. Pierre Bourdieu) points out the relationship that an organisation holds with its environment. The latest paradigm in social sciences is represented by network analzses which provides frameworks both for studying the internal functioning of organisations as well as for the relationships between the organisations and their environment.